Исследование возможности организации культурного агорболотоводства на месторождении торфа «Михановичи» - Казанович, К. А. (БНТУ, 2021)
А project for the study of the Mikhanovichi peat deposit was presented in order to identify the possibility of organizing sites for the cultivation of medicinal bog berries.The sites will be established by studying vegetation using modern satellite maps and GWL-monitoring.